2015
DOI: 10.1097/scs.0000000000002179
|View full text |Cite
|
Sign up to set email alerts
|

Customized Titanium Mesh for Repairing Cranial Defects

Abstract: Titanium cranioplasty is one of the well-established and widely used techniques for repairing cranial defects. In this paper, we present an improved way to design and create titanium meshes with more evaluation process. Computed tomography scan data of patients were used to create three-dimensional virtual models. Implants were designed with NX ImageWare 13.2 (Siemens PLM Software, Plano, TX). Final titanium meshes were assessed by Geomagic Studio 12 (Geomagic, Inc., Morrisville, NC) and NX ImageWare 13.2.Tita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In oral implant surgery, titanium mesh plays an important role in the bone reconstruction in patients with large area or multiple tooth position jaw defects. Titanium mesh acts as a mechanical barrier membrane and it essentially acts as a "tent" to provide a su cient low pressure space for the formation of new bone in alveolar ridge incremental surgery, which is conducive to the regeneration and repair of large-area bone defects [13,14]. Recent studies have shown that titanium mesh effectively ensures that patients with bone defects obtain su cient bone increment.…”
Section: Discussionmentioning
confidence: 99%
“…In oral implant surgery, titanium mesh plays an important role in the bone reconstruction in patients with large area or multiple tooth position jaw defects. Titanium mesh acts as a mechanical barrier membrane and it essentially acts as a "tent" to provide a su cient low pressure space for the formation of new bone in alveolar ridge incremental surgery, which is conducive to the regeneration and repair of large-area bone defects [13,14]. Recent studies have shown that titanium mesh effectively ensures that patients with bone defects obtain su cient bone increment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore,functional restorationis achieved through those devices [1]. From those is obtained a surer, shorter and timepredictable surgery [2].…”
Section: Introductionmentioning
confidence: 99%
“…Third, evaluatethe accuracy of the PSI compared with the biological surface. Fourth, piece evaluation [2]. The development of those steps in the process of PSI deviceinvolve tools such asreverse engineering (RE), computer-aideddesign -manufacturing-engineering (CAx), 3D modeling, and rapid prototyping (RP) techniques [6], [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation